Study of size mismatches effect on transport properties in Cu-Sb and Cu-Sn liquid alloys - Singh, B. P.; Singh, B. K.; Jha, I. S.; Shrestha, G. K.; Koirala, I.; Adhikari, D. (BIBECHANA, 2014)
We report a formalism that connects thermodynamics and transport properties such as viscosity and diffusion coefficient which has been used to calculate the concentration dependence of free energy of mixing, concentration-concentration fluctuations in the long wavelength limit and concentration dependence of diffusion and viscosity in Cu-Sb and Cu-Sn binary liquid alloys at 1190K and 1400K respectively with aid of size effect and no size effect. Our calculations show that a reasonable degree of chemical order exists in both alloys system. It can be concluded that size mismatch has more effects on the transport properties of Cu-Sb hetero-coordinated system with greater size ratio than Cu-Sn hetero-coordinated system. DOI: http://dx.doi.org/10.3126/bibechana.v12i0.11781 BIBECHANA 12 (2015) 96-103